Trend analysis of the development of Indonesian local disaster: A bibliometric study - Aminkun Imam Rafii (Himpunan Pengembang Kurikulum Indonesia (HIPKIN), 2024)
This study aims to analyze trends in the development of disaster education studies in Indonesia by considering the literature and its implementation. Bibliometric and network analysis is carried out based on the visualization of research trends in disaster education in Indonesia. Based on 35 articles analyzed, the result shows that disaster education has received increasing attention from researchers in recent years. Then, research mainly focused on simulation-based disaster education and limited training. However, this trend in disaster education research has overgrown since mid-2016 and will peak in 2022. This study also involves geographic mapping of disaster education research in several regions of Indonesia. The findings show that Central Java is the main focus of the study. However, the research also involves other areas in Indonesia vulnerable to disasters, such as Aceh, South Sumatra, North Sumatra, Jakarta, East Java, Sulawesi, and Jayapura. This study also found that disaster education literature's dominant discussion trend is